Gênero e práticas de produção dos alunos da educação de jovens e adultos - Fernandes, Alaide Aparecida dos Santos (2007)
This doctorate research carried out in the Postgraduate Studies Program of the São Paulo Pontifícia Universidade Católica, studies the discursive text genres restricted to the production activities of students from 5th to 8th grades of the elementary school, at the Education for Youths and Adults (EJA) level. The general objective of this research is to contribute to a more adequate teaching of language activities, through the conciliation of the sociodiscursive theories with text production practices. The specific objectives are: 1) identify the predominant textual genres in discursive activities of the EJA students; 2) identify structural and functional characteristics of these genres; 3) present a proposal for the teaching of reading for these students, based on the data obtained by this research. This research is justified because, currently, there is a sociointeractionist trend in the studies of language, recommending that language teaching-learning should be based on the teaching of textual genres. This way, the National Curricular Parameters (PCN), official document, which guides the elaboration of pedagogical proposals at schools, proposes a systematization of determined genres. Based on the hypothesis that the speakers of a language do not use the same discursive textual genres, we understand that it is necessary to identify the genres that permeate the discursive practices of the EJA students and, afterwards, study them to know them better and apply them, didactically, in the teaching of the mother language. Two areas provide theoretical basis for this research: the Text Linguistic and the Discourse Linguistic. The first has supplied the basis for the study of the linguistic and textual genre mechanisms and the second has subsidized the study of the discursive complexity based on which the genres are constituted. The results obtained allow the possibility to extend a second thought to the production practices under the perspective of two textual genres: the flyers and the news